2016
DOI: 10.1099/mic.0.000302
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Lactobacillus strains as potential probiotics for vaginitis treatment

Abstract: Jos e de las Lajas Mayabeque, CubaLactobacilli are the dominant bacteria of the vaginal tract of healthy women, and imbalance of the local microbiota can predispose women to acquire infections, such as bacterial vaginosis (BV) and vulvovaginal candidiasis (VVC). Although antimicrobial therapy is generally effective, there is still a high incidence of recurrence and increase of microbial resistance due to the repetitive use of antimicrobials. Thus, it has been suggested that administration of probiotics incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 38 publications
3
48
0
11
Order By: Relevance
“…Biofilm formation was assessed using the crystal violet assay as described by Santos et al . [51] and auto-aggregation as described by Younes et al [52]. Antimicrobial activity against Neisseria gonorrhoeae was assessed by challenging N. gonorrhoeae (WHO-L strain) with varying (neutralized with NaOH to pH 7.0) dilutions of L. crispatus supernatants.…”
Section: Methodsmentioning
confidence: 99%
“…Biofilm formation was assessed using the crystal violet assay as described by Santos et al . [51] and auto-aggregation as described by Younes et al [52]. Antimicrobial activity against Neisseria gonorrhoeae was assessed by challenging N. gonorrhoeae (WHO-L strain) with varying (neutralized with NaOH to pH 7.0) dilutions of L. crispatus supernatants.…”
Section: Methodsmentioning
confidence: 99%
“…strains have been isolated from healthy women and their potential as probiotics has been investigated. L. plantarum and L. fermentum strains isolated from healthy Cuban women exhibited antagonic activity against G. vaginalis, C. albicans, as well as remarkable adhesive capacities and lactic acid production [134]. Similarly, L. fermentum 9LB6, 4LB16, and 10LB1 and L. plantarum 9LB4 strains were isolated from Algerian women and suggested as probiotic candidates based on their relevant inhibitory activity of pathogens, lack of hemolytic capability and other beneficial properties according to in vitro studies [135].…”
Section: Probiotics and Microbiota Manipulationmentioning
confidence: 99%
“…The inhibition of these virulence factors in C. albicans is an important tool for the treatment of candidiasis. Several studies in the literature showed that some Lactobacillus strains were able to inhibit C. albicans through the production of bacteriocins, environmental alterations through the production and secretion of molecules arising from the metabolism of lactic acid and hydrogen peroxide, or even by mechanical inhibition of adhesion receptors (Orsi et al 2014;Leão et al 2015;Santos et al 2016;Wannun et al 2016). Probiotic bacteria are also capable of modulating the immune systems of their hosts through the production of cytokines and the stimulation of cellular activity (Mendonc ßa et al 2012;Shibasaki et al 2014;Roy et al 2015).…”
Section: Introductionmentioning
confidence: 99%